What kind of European banking union? - Jean Pisani-Ferry; André Sapir; Nicolas Véron; Guntram B. Wolff (Bruegel, 2012)
This paper discusses the creation of a European Banking Union. First, we discuss questions of design. We highlight seven fundamental choices that decision makers will need to make: Which EU countries should participate in the banking union? To which categories of banks should it apply? Which institution should be tasked with supervision? Which one should deal with resolution? How centralised should the deposit insurance system be? What kind of fiscal backing would be required? What governance framework and political institutions would be needed?
Keywords: 330; Bankenpolitik; Bankenaufsicht; Bankensystem; Einlagensicherung; Europäische Wirtschafts- und Währungsunion; EU-Staaten